A population specific mitochondrial intron from the sponge Phakellia robusta in the North-East Atlantic. (June 2021) - Cranston, Alex; Taboada, Sergi; Koutsouveli, Vasiliki; Schuster, Astrid; Riesgo, Ana
Abstract: Self-splicing mitochondrial introns are a rarely reported phenomenon in animals, with a sparse and uneven distribution confined to some species of sponges, corals, placozoans, and a single species of annelid. Here, we describe a mitochondrial intron present only in some populations of Phakellia robusta, a sponge distributed across the North-east Atlantic deep-sea. The mitochondrial intron of P. robusta was detected in the position 387 of the COI gene and classified as a Group I intron of class IB. Interestingly, this intron was only detected in the shallower populations of P. robusta from Ireland to Norway, spanning 1000 km and was absent in deeper samples of the species. Such deeper populations have recently been proposed to be the result of hybridization between P. robusta and its congeneric Phakellia hirondellei . We propose that this past hybridization might be behind the absence of the intron in the specimens of P. robusta occurring at deep waters. Our analyses indicate that the intron detected in P. robusta might have a double origin (most likely fungi and other organism), as it has previously suggested for the sponge Stupenda singularis . BLAST searches produced matches with the homing endonuclease gene (HEG) nested within the S. singularis intron and this HEG belongs to the family of LAGLIDADG homing endonucleases (LHEs). The evolutionary relevance of the presence/absence of this intron for this species needs to be determined and potential adaptive advantages should not be ruled out. Highlights: New intron 387 in the COI gene of the marine demosponge Phakellia robusta and classified as a Group I intron of class IB. Similar intron to other demosponges, with a double origin (fungi and some other organism), but acquired by HGT independently. Intron present only in the deeper populations of Phakellia robusta of their North Atlantic distribution range. Possible presence of intron as a result of hybridisation between Phakellia robusta and its sister species P. hirondellei.